(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, there is a lot of development in technology. Also, people have become busier and businesses as well as jobs have also shifted to internet. People have got less time and even some people who got enough time find it difficult to search someone to solve their common household problems. Additionally, it is very challenging for lower class to find a job that perfectly fits their skill set. In this article, our team has explained about a solution for these two major problems which is - "Kaamkarao.com". This is a web as well as an android application that allows every Indian to register as a client or a freelance employee. So, clients can easily get multiple options who can do their common household jobs and unemployed individuals can also get work from this application. The registered details are saved in Firebase Real-time Cloud Database after verification and then authorised person can access that account using contact number and password. There is also a Hindi language option available with application which will be helpful to anyone who do not know English. This article also shares details about survey carried out among different age groups, genders and classes of society and their problems in this regard.